Numerical modeling of fluid flow with rafts: An application to lava flows. (July 2016) - Tsepelev, Igor; Ismail-Zadeh, Alik; Melnik, Oleg; Korotkii, Alexander
Highlights: Multi-phase fluid flows with rigid rafts are modeled. Fluid flow is analyzed on horizontal and topographic surfaces. Distribution of rafts depends on boundary conditions and raft landing scenarios. Flow with rafts through an inclined channel helps to analyze lava advances. Fluid effusion with varying properties may assist in field interpretations. Abstract: Although volcanic lava flows do not significantly affect the life of people, its hazard is not negligible as hot lava kills vegetation, destroys infrastructure, and may trigger a flood due to melting of snow/ice. The lava flow hazard can be reduced if the flow patterns are known, and the complexity of the flow with debris is analyzed to assist in disaster risk mitigation. In this paper we develop three-dimensional numerical models of a gravitational flow of multi-phase fluid with rafts (mimicking rigid lava-crust fragments) on a horizontal and topographic surfaces to explore the dynamics and the interaction of lava flows. We have obtained various flow patterns and spatial distribution of rafts depending on conditions at the surface of fluid spreading, obstacles on the way of a fluid flow, raft landing scenarios, and the size of rafts. Furthermore, we analyze two numerical models related to specific lava flows: (i) a model of fluid flow with rafts inside an inclined channel, and (ii) a model of fluid flow from a single vent on an artificial topography, when the fluid density, its viscosity, and the effusion rate vary with time. Although the studied models do not account for lava solidification, crust formation, and its rupture, the results of the modeling may be used for understanding of flows with breccias before a significant lava cooling.